Validity and Limited Trial of Physics Learning Tools Based on the Ethnoscience-Integrated Inquiry-Creative-Process Model to Improve Prospective Physics Teachers’ Critical Thinking Skills - Ni Nyoman Sri Putu Verawati; Ahmad Harjono; Wahyudi Wahyudi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to describe the validity and limited trial results of physics learning tools based on the ethnoscience-integrated Inquiry-Creative-Process (ICP) model to improve prospective physics teachers’ critical thinking skills. This research employed a development research design and produced semester learning plans and learning scenarios, teaching materials or modules, and a critical thinking test instrument. The learning tools were validated by three expert validators based on content validity and construct validity. The limited trial used a one-group pretest-posttest design involving 29 prospective physics teachers. Data were analyzed descriptively using mean scores and n-gain, and inferentially using a paired sample t-test and the Wilcoxon signed-rank test. The validation results showed an average content validity score of 4.05 and an average construct validity score of 3.99, both categorized as valid. The limited trial results showed that the CTs score increased from 10.41 to 25.55 with an n-gain of 0.70. The average CTi score also increased from 1.30 to 3.19 with an n-gain of 0.70. The increase in CTs was significant based on the paired sample t-test, while all CTi indicators showed significant improvement based on the Wilcoxon signed-rank test. These findings indicate that physics learning tools based on the ethnoscience-integrated ICP model are valid and can improve prospective physics teachers’ critical thinking skills in a limited trial context.